Edukasi Pencegahan Kekurangan Energi Kronik pada Remaja dalam Upaya Penurunan Stunting - Jaelani, Sri; Sitawati, Sitawati (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2024)
Chronic Energy Deficiency (KEK) is a condition where teenagers experience a prolonged or chronic lack of iron (calories and protein). According to the UNICEF statement, the causes of stunting are nutritional imbalances, low birth weight and a history of any disease suffered by the mother during pregnancy, such as chronic energy deficiency. Many young women suffer from a lack of energy and protein intake. Low intake of micronutrients. Nationally, the prevalence of chronic energy deficiency is 20.8% in women of childbearing age, 6.8% in underweight women aged 13 to 15 years and 1.9% in very thin women. Nutrition education is a method and effort to increase nutritional knowledge and eating behavior to create knowledge and attitudes towards nutrition among teenagers. The higher the nutritional knowledge, the greater the influence on attitudes and behavior towards food intake. The factors that can cause stunting in toddlers are closely related to each other. The prevalence of stunting in teenagers is due to the fact that the rate of chronic energy deficiency in teenagers is still high. There were 40 participants who took part in the activity. By using leaflet media which was distributed to all teenagers who took part in the socialization. It is hoped that after carrying out this activity, teenagers will increase their knowledge and understanding and will be motivated to maintain their health by always consuming blood-boosting tablets (TTD) and consuming nutritious food with the aim of preventing chronic energy deficiency in teenagers